Subtractive bilingualism in teaching and learning through the medium of English without the support of the mother tongue - Ramokgopa, Marothi Kotsile (My University, 2011)
This research study investigated subtractive bilingualism in teaching and learning through the medium of English without the support of the mother tongue. The aim was to investigate if it is possible for learners to acquire a second language (English) without totally losing their home language. This was done through: probing the reasons why the language policy is difficult to implement in schools as outlined by the constitution of South Africa; determining the causes of subtractive bilingualism in the school settings and; an emphasis of the rights and responsibilities of educators and parents to make a positive difference in the lives of bilingual and bicultural learners. This research was grounded on Cummins (1991) theory of second language acquisition. The literature review examined other theories of second language acquisition and learning (Krashen 1981). In particular, emphasis was placed on the following broad areas in the literature review: mother tongue development; language shift and language loss; language planning and language policy; language and culture; language and identity, attitudes and equity; language in education; the National Language Policy Framework; and multilingualism. This research was conducted using the qualitative research methodology. A case study design was employed. Three instruments were used for collecting of the data. These were: questionnaires, interviews and classroom observations. The data analysis strategy used in this research was interaction analysis which was done through transcriptions of observations and video and audio recordings of interviews and classroom observations. The following were some of the findings from this research study: learners were not happy with their educators who unduly force them to communicate in English as the educators themselves are also not proficient in the language; learners are afraid to take risks of communicating in English for fear of other learners intimidating them; and many learners now communicate only in English and cannot understand the greater details of their mother tongue. The recommendations of this study are: to reduce the extent of language loss, parents should establish a strong home language policy and provide ample opportunities for children to expand the functions for which they use the mother tongue; parents and care-givers should spend time with their children and tell stories or discuss issues with them in a way that develops their mother tongue vocabulary and concepts so that children come to school prepared to learn the second language successfully without being distracted; funding and resources must be made available for additional language acquisition; well-trained and dedicated teachers with similar linguistic backgrounds to the learners should be hired; and the new language policy should be adopted
Thesis (M.ED (Language Education)) --University of Limpopo, 2010
Keywords: Bilingualism; Teaching; Learning; 370.1175; Teaching and learning